THE EFFICIENCY OF THE ECONOMICS OF TAXES AND BALANCES OF PAYMENTS IN THE DEVELOPMENT OF FOREIGN ECONOMIC ACTIVITY - Sharipov, F.G. (Innovative Development in Educational Activities, 2023)
The article is devoted to the main groups of foreign economic functions and types and elements of foreign economic activity and their characteristics. Moreover, it also describes efficiency of the economics of taxes, balances of payments in the development of foreign economic activity.